Participation Ladder in Business Incubation Program - Priyo Utomo; Arif Dharmawan; Zakariya Zakariya; Rudy Handoko (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Purpose: The government's efforts in developing the economy of low-income communities in the city of Surabaya require high participation support. The low community participation in the incubation facilitation program for independent businesses is a problem that needs a solution